2016
DOI: 10.4103/2249-4863.197258
|View full text |Cite
|
Sign up to set email alerts
|

Urinary tract cancers: An overview for general practice

Abstract: Urinary tract cancers are common and comprise a gamut of lesions ranging from small benign tumors to aggressive neoplasms with high mortality. The predominant urinary tract malignancy is bladder cancer. The clinical challenge is early detection and adequate follow-up because recurrence is high and delayed diagnosis is associated with poor prognosis. Primary care physicians form a key part of the management apparatus for these patients and may be responsible for ensuring adequate ongoing surveillance. This arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…Therefore, WGCNA is usually used to facilitate the screening or identification of candidate biomarkers or therapeutic targets. Tumor node metastasis (TNM) 2009 (7th edition) was recommended for the BC, and previous studies demonstrated that patients with an infiltrative pattern had better survival than those with other pattern types (PDQ Adult Treatment Editorial Board, 2002 ; Yaxley, 2016 ). In the present study, the WGCNA algorithm was applied to identify candidate biomarkers for BC based on the TNM staging of BC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, WGCNA is usually used to facilitate the screening or identification of candidate biomarkers or therapeutic targets. Tumor node metastasis (TNM) 2009 (7th edition) was recommended for the BC, and previous studies demonstrated that patients with an infiltrative pattern had better survival than those with other pattern types (PDQ Adult Treatment Editorial Board, 2002 ; Yaxley, 2016 ). In the present study, the WGCNA algorithm was applied to identify candidate biomarkers for BC based on the TNM staging of BC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Prostate cancer, renal cancer and urothelial carcinoma are common types of malignancies worldwide [ 2 ]. Although the underlying mechanism of its development is largely unclear, it has been widely accepted that environmental risk factors such as cumulative cigarette smoking, alcohol consumption, certain occupational exposures, radiation and possible carcinogens including N-nitrosamines, aniline, vinyl chloride and urethane are involved in the onset of urinary cancer [ 3 ]. Nevertheless, very small fraction of individuals who exposed to the risk factors eventually become urinary cancer patients, indicating that other causes, such as genetic susceptibility, might affect the variat individual urinary cancer risk [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lack of reliable genetic markers hinders therapeutic decision‐making and causes substantial problems in diagnosis, prognosis and management. Early detection and adequate follow‐up are the clinical challenges due to recurrence being frequent and deferred diagnosis being associated with poor prognosis . Therefore, it is required to identify potential biomarkers with better correlations to malignancy development and/or medication outcomes in UTUC and UBUC patients.…”
mentioning
confidence: 99%